2008 Symposium on VLSI Technology 2008
DOI: 10.1109/vlsit.2008.4588591
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tantalum composition in TaC/HfSiON gate stack on device performance of aggressively scaled CMOS devices with SMT and strained CESL

Abstract: We report TaC x /HfSiON gate stack CMOS device with simplified gate 1 st process from the viewpoints of fixed charge generation and its impact on the device performance. Moderate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…10, a lower PEALD temperature can suppress the side-edge oxidation of a metal gate electrode and a high-k dielectric during PEALD, leading to the improvement in I on -I off characteristics. 26) In order to further improve I on -I off characteristics, the ALD-SiO film deposited at 100 C was used as an OSS film. As the result, the I on of the nMOSFET with the ALD-SiO OSS film deposited at 100 C was 12% higher than that of the nMOSFET with the ALD-SiO OSS film deposited at 200 C. This result indicates that a lower deposition temperature of a SiO OSS film is effective for improving I on -I off characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…10, a lower PEALD temperature can suppress the side-edge oxidation of a metal gate electrode and a high-k dielectric during PEALD, leading to the improvement in I on -I off characteristics. 26) In order to further improve I on -I off characteristics, the ALD-SiO film deposited at 100 C was used as an OSS film. As the result, the I on of the nMOSFET with the ALD-SiO OSS film deposited at 100 C was 12% higher than that of the nMOSFET with the ALD-SiO OSS film deposited at 200 C. This result indicates that a lower deposition temperature of a SiO OSS film is effective for improving I on -I off characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the strain effects in short channel devices are enhanced by eliminating fixed charges inside HfSiON [73] , which is also material dependent. And the reliability issue of strained channel device has been investigated.…”
Section: Mobility Enhancement Technologymentioning
confidence: 99%
“…Not only gate leakage current but also mobility has been improved by material selection and interface layer modulation under metal-gate/high-k [1]. However, the last issue still remaining is reliability problems.…”
Section: Introductionmentioning
confidence: 99%
“…High-k gate dielectrics has emerged as replacement for the conventional SiON gate oxides because it can reduce gate leakage significantly but also accelerates scaling-down of the equivalent oxide thickness (EOT) at the same time. Not only gate leakage current but also mobility has been improved by material selection and interface layer modulation under metal-gate/high-k [1]. However, the last issue still remaining is reliability problems.…”
Section: Introductionmentioning
confidence: 99%